THEORETICAL AND PRACTICAL BASIS OF IMPROVING INNOVATIVE APPROACHES IN THE PROCESS OF IMPLEMENTING DIGITAL MARKETING TECHNOLOGIES IN SMALL BUSINESS SUBJECTS (Marketing Journal, 2025)
This paper explores the practical implementation of digital marketing technologies in small business entities and evaluates the level of innovative approaches applied. Based on data collected through surveys and interviews, the study assesses the use of di gital platforms, the quality of customer interactions, and readiness for digital transformation. The analysis reveals that while small businesses show interest in digital tools, they face challenges in using them systematically and effectively due to a lac k of skills and technical resources. Practical recommendations were developed based on the identified issues and opportunities. № 10-SON OKTA BR, 2025 -YIL 329
Keywords: digital marketing; small business; innovative approach; transformation; strategy; customer interaction; platforms